Noninvasive Testing for Carotid Artery Stenosis: I. Prospective Analysis of Three Methods - O'Leary, Daniel H.; Persson, Alfred V.; Clouse, Melvin E. (American Journal of Neuroradiology, 1981)
Oculoplethysmography-carotid phonoangiography and periorbital directional Doppler sonography are two techniques widely used in the noninvasive evaluation of possible carotid artery disease. Recent advances with sonographic Doppler devices now permit measurement of blood velocities in the extracranial carotid arteries by direct scanning with a color coded Doppler imaging system. A prospective study involving 216 patients being evaluated for possible carotid insufficiency was carried out to compare the results obtained with these three methods. With stenosis 65% or greater at angiography, the accuracy of the Doppler imaging system was 94%, that of oculoplethysmography-carotid phonoangiography was 84%, and that of periorbital directional Doppler sonography was 80%. These results demonstrate that direct Doppler examination of the carotid bifurcation is superior to either of the other two techniques for the detection of carotid artery stenosis.